Location Detection Using Wifi - Ali, MohdKhair (Universiti Teknologi Petronas, 2006)
There are many approaches for indoor location detection such as using infrared and ultra sound. Beside that, another powerful approach for indoor location detection is RF (Radio Frequency). In emergency situation happened in a building such as fires, it is difficult to make sure all people in the building have left out. It is even worst if there are victim trapped but no body know where the exactly location of the victims. The project is construct a network environment based on wireless LAN infrastructure and supports the protocol over the 802.1 lg. The system is organized by client-server, access points and PDAs or laptops as client devices. Location determination method is implemented on the basis of signal strength. The test program developed using the sample provided able to detect the access points available. The parameter that can be get using the program including the SSID, MAC address, Network type, WEP, RSSI and etc. To identify the distance testing has been made based on the RSSI gathered. The testing is made by calculating manually the distance of the location based on the RSSI collected. The proposed system is an indoor positioning system based on signal strength measurements, which were approximated by the received RSSI in a mobile device. The triangulation method combined with distance estimation is used to predict the position of the terminal. It is hoped that with some improvement to the proposed system able to work in the emergency condition